Private policing - Button, Mark (Routledge, 2019)
What is private policing? -- Explaining private policing -- "Extreme profitshire" revisited : the public police and privatisation -- State public policing bodies (non-police) -- Specialised police organisations -- Non-governmental organisations and policing -- Voluntary policing -- The private security industry and policing -- Corporate security management -- Security officers and policing -- Plural policing the case of patrol -- Private investigation and policing -- The regulation of private policing -- Private policing: concluding comments -- Index